Hollow mesoporous silica nanosphere-supported FePt nanoparticles for potential theranostic applications. Issue 36 (6th September 2017) - Lin, Chih-Yu; Li, Wei-Peng; Huang, Shao-Peng; Yeh, Chen-Sheng; Yang, Chia-Min
Abstract : A nanocomposite comprising FePt nanoparticles and hollow mesoporous silica nanospheres has been fabricated for MRI, NIR photothermal therapy and combined chemo-/thermotherapy. Abstract : A facile preparation of a nanocomposite comprising FePt nanoparticles (NPs) and hollow mesoporous silica nanospheres (HMSNs) was reported. The bimetallic NPs had an alloy structure with Pt-rich cores and were highly dispersed on the mesoporous shell of HMSNs. The material, designated as FePt@MMT-2, could be gradually degraded and dissolved under physiological conditions and showed low cytotoxicity against HeLa cells. FePt@MMT-2 exhibited ferromagnetic-like properties and broadband near-infrared (NIR) absorption along with high photothermal transduction efficiency. In addition, in vitro studies showed high efficacy of FePt@MMT-2 in killing HeLa cells with 1064 nm NIR irradiation, and synergistic anticancer effects when combined with chemo drug topotecan. The results demonstrated the potential of the designed nanocomposite for theranostic applications.